The relationship between services quality and international student's satisfaction in higher education institution - Yew, Yit Hooi, 1981-; Ahmad Jusoh, supervisor; Fakulti Pengurusan dan Pembangunan Sumber Manusia (2010)
Thesis (Sarjana Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2010